Novel risk group stratification for metastatic urothelial cancer patients treated with immune checkpoint inhibitors - Julie M. Shabto; Dylan J. Martini; Yuan Liu; Deepak Ravindranathan; Jacqueline Brown; Emilie E. Hitron; Greta A. Russler; Sarah Caulfield; Haydn Kissick; Mehrdad Alemozaffar; Kenneth Ogan; Wayne B. Harris; et al. (Cancer Medicine)
Abstract Background We developed a novel risk scoring system for urothelial cancer (UC) patients receiving immune checkpoint inhibitors (ICI). Methods We conducted a retrospective review of 67 UC patients treated with ICI at Winship Cancer Institute of Emory University from 2015 to 2018. Using stepwise variable selection in Cox proportional hazard model and Sullivan's weighting schema, baseline platelet‐to‐lymphocyte ratio (PLR), presence of liver metastasis, baseline albumin, and baseline Eastern Cooperative Oncology Group performance status (ECOG PS) were used for risk scoring. Patients were categorized into good risk (risk score 0‐1), intermediate risk (risk score 2‐3), and poor risk (risk score 4‐6). Univariable (UVA) and multivariable analysis (MVA) and Kaplan‐Meier method were used to assess overall survival (OS) and progression free survival (PFS). Results The Emory Risk Scoring System had C‐statistics of 0.74 (Standard Error = 0.047) in predicting OS and 0.70 (Standard Error = 0.043) in predicting PFS. Compared to good risk patients, poor risk patients had significantly shorter OS and PFS in both UVA and MVA (all P < .001), and intermediate risk patients had significantly shorter OS and PFS in both UVA and MVA (all P < .03). Conclusions Risk scoring using baseline PLR, presence of liver metastasis, baseline albumin, and baseline ECOG PS may effectively predict OS and PFS in UC patients receiving ICI.